Territorialization of public policies in vulnerable territories in Londrina/Paraná/Brazil: Challenges and advances - Silva, Izabelle Cristina Gusmão da; Mantovan, Heloisa Maria; Veiga, Léia Aparecida; Cunha, Caio Cezar; Antonello, Ideni Terezinha (National Journal of City Management, 2024)
This research aims to reflect on the scope of public health, epidemiology and social assistance policies in vulnerable territories in the North Zone of Londrina-PR, represented by the vulnerable territories (favelas) called Aparecidinha and Flores do Campo, in 2023, based on the work of CRAS Norte A and Norte B, the Department of Epidemiology and Health Information (DEPIS) and the municipal Health Department. This is a qualitative study, based on a survey of secondary information (scientific literature and official documents). It was found that health, epidemiology and care have faced challenges such as: guaranteeing the management of policies in accordance with the law, maintaining the efficiency of the services provided and tackling complex social problems in the face of the reality experienced by the population. The conclusion is that the social context in the areas of socio-economic vulnerability and lack of ownership of urban land in the North Zone of Londrina makes it very difficult to conduct and implement public policies that are essential for the quality of life of families, particularly those that fall under the Department of Epidemiology and Health Information (DEPIS).
Keywords: Public policy; Vulnerable territory; Quality of life